The contribution of glutathione to the destabilizing effect of yeast on wheat dough. (15th April 2015) - Verheyen, C.; Albrecht, A.; Herrmann, J.; Strobl, M.; Jekle, M.; Becker, T.
Highlights: In 21 commercial yeast samples 1.2–81.2 mg glutathione was detected. The glutathione content of yeast depends on the proportion of dead cells. Glutathione is responsible for the dough weakening effect of yeast. Raising agents are suitable to determine effects of yeast metabolites on leavening. Abstract: Any factor which impairs the development of the gluten network affects the gas retention capacity and the overall baking performance. This study aimed to examine why rising yeast concentrations ( Saccharomyces cerevisiae ) decrease the dough elasticity in an asymptotic manner. Since in 27 commercial fresh and dry yeasts up to 81 mg glutathione (GSH) per 1 g dry sample were found. Through the addition of reduced GSH in dough without yeast, the extent of dough weakening was analysed. Indeed rheological measurements confirmed that yeast-equivalent levels of GSH had a softening effect and during 3 h fermentation the weakening coefficient increased from 0.3% to 20.4% in a Rheofermentometer. The present results indicate that free –SH compounds, as represented by GSH, considerably contribute to the softening of dough through dead yeast cells.